Tabulated Chemistry Models for Numerical Simulation of Combustion Flow Field - Masaya Muto (Fluids)
In numerical simulations of combustion flow fields, tabulated chemistry models are widely used to reduce computational cost compared to rigorous reaction calculation methods such as detailed chemical reaction calculations. Tabulated combustion data are generated by performing low-dimensional combustion calculations prior to simulating the combustion flow field. The results are then stored in a database indexed by parameters such as mixture fraction and reaction progress variables. In recent years, significant advancements have been made in the tabulation of combustion data to accommodate diverse fuels and replicate the complex conditions observed in practical combustion systems. This review paper provides an overview of recent developments in tabulated chemistry models, particularly those based on the flamelet/progress-variable method. It specifically addresses scenarios involving multi-point fuel injection, the presence of heat loss factors in combustion flow fields, the consideration of varying diffusion coefficients, and other complex phenomena.